Selection of The Construction of The Seed Drill for Seeding Wheat Seeds in The Space Between Rows of Cotton Plant - Xudoyberdiev, T.S.; Boltaboev, B.R.; Abdullaev, D.A.; Kalashnikov, V.A. (International Journal of Psychosocial Rehabilitation, 2020)
At the present time, when more than 65% of the wheat sown area in the Republic is seeded in the space between rows of cotton plant, it remains a problem to develop a design of such a seed drill that would allow to seed wheat seeds in the space between rows of cotton plant. The analysis of the design of existing seed drills for seeding gourds and vegetables, as well as seed drills of wheat and cotton was determined that they are not suitable to seed in the space between rows of cotton plant and it requires to develop a new design of the seed drill for high-quality seeding of wheat seeds in the space between rows of cotton plant. The proposed design of the seed drill, consisting of independently working sections for each row spacing, ridges mounted on two support wheels, coulters and hoppers, is distinguished by its design simplicity and relatively less traction resistance.